Memaknai sesamaku manusia dengan kasih inkarnatif di era Sociaety 5.0 menurut Lukas 10:25-37 - Lau, Anika Regina; Samosir, Verawati Dosmaria; Koagouw, Deisy Yona (MEFORAS: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
The parable of the good Samaritan in Luke 10:25-37 emphasizes incarnate love that transcends ethnicity, religion, and social status. The 5.0 era has created a new civilization in human life, where the world is digitally connected but gives birth to a highly individualistic nature in human life. Therefore, understanding the meaning of "my neighbor with incarnate love" is very important to understand and apply in the lives of believers in the digital era. This article aims to examine Christian values in Luke 10:25-37 and tries to trace their relevance in shaping the lives of believers amidst the challenges of digitalization and social dehumanization. Through a theological study of "my neighbor" using a descriptive analysis method of Luke 10:25-37, the author offers a new understanding of how believers can live in incarnate love with their fellow human beings in the midst of an increasingly connected yet individualistic world.